OPTIMASI PRODUKTIVITAS SUMUR X MELALUI ANALISIS PENGGUNAAN SISTEM GAS LIFT DENGAN PENDEKATAN SOFTWARE KOMERSIAL - Erlely, Roberth; Chandra, Steven; Silahooy, Stevi (Petro : Jurnal Ilmiah Teknik Perminyakan, 2024)
Decreased well productivity is a common problem in the petroleum industry caused by decreased flow rates and reservoir pressure. One solution to overcome this problem is the use of artificial lift, namely the gas lift method. Gas lift is a method that injects high-pressure gas into the well to reduce hydrostatic pressure, allowing the fluid to rise to the surface. This study aims to analyze the effectiveness of the gas lift system in increasing the productivity of well X using commercial software. The method used in the research is a quantitative method with the help of commercial software used as a data processing tool. The results showed that the optimum production rate that can be achieved at well X is 378.32 STB/day with an optimum gas injection rate of 0.3 MMscf/day. In addition, several parameters affecting well productivity were analyzed, namely water cut, reservoir pressure, and gas injection rate where it was found that every 10% increase in water cut caused a decrease in production of 40-43 STB/day, while a decrease in reservoir pressure to 500 psig decreased production from 435.5 STB/day to 162.3 STB/day. Increasing the gas injection rate is proven to increase oil production, but there is an optimal limit to avoid increasing operational costs that are not balanced with increased production.